Foundation of Al-Hikmah al-Mutaaliyah: Ontology and Epistemology on Philosophy of Mulla Sadra - Miswari Miswari (At-Tafkir, 2026)
This article aims to discuss the basic principles of Mulla Sadras thinking, namely his ideas about ontology and epistemology. This qualitative research uses library data, especially references written by Mulla Sadra and works that have been written about his thoughts. The findings of this article prove that Mulla Sadras main ontology discusses the difference between wujud and mahiyah. This discussion is very important to determine which is the essence of reality, because the nature of reality is one. In Mulla Sadras thought, wujud is more fundamental than wujud in external reality, although in the mind, wujud is more fundamental than wujud. Because mahiyah is only a barrier for the wujud that is formed by the mind. Wujud is the single foundation for external reality. In the epistemological system of Mulla Sadras teachings, an important focus is the difference between knowledge through confirmation (hushuli) and knowledge through presence (hudhuri). Mulla Sadra emphasized that hudhuri is more valid than hushuli. He concluded that hushuli was actually hudhuri. Mulla Sadras philosophy was heavily influenced by many previous philosophers, especially Ibn Sina, Syihab al-Din al-Suhrawardi, and Ibn Arabi.